Distinct genome stabilization procedures lead to phenotypic variability in newly generated interspecific yeast hybrids - Murath, Pablo; Hoffmann, Stephanie; Herrera-Malaver, Beatriz; Bustamante, Luis; Verstrepen, Kevin; Steensels, Jan (Frontiers in Microbiology, 2025)
Yeast cells sometimes engage in interspecific hybridization, i.e., crosses between different species. These interspecific yeast hybrids combine phenotypes of the two parental species and can therefore allow fast adaptation to new niches. This is perhaps most evident in beer yeasts, where a cross between Saccharomyces cerevisiae and Saccharomyces eubayanus led to the emergence of the lager yeast Saccharomyces pastorianus, which combines the fermentation capacity of S. cerevisiae with the cold tolerance of S. eubayanus, making the hybrid suitable for the typical cool lager beer fermentation conditions. Interestingly, however, merging two different genomes into one cell causes genomic instability and rearrangements, ultimately leading to a reorganized but more stable hybrid genome. Here, we investigate how different parameters influence this genome stabilization trajectory and ultimately can lead to variants with different industrial phenotypes. We generated seven de novo interspecific hybrids between two S. eubayanus strains and an ale S. cerevisiae strain, subsequently exposing them to three different genome stabilization procedures. Next, we analyzed the fermentation characteristics and metabolite production of selected stabilized hybrids. Our results reveal how variation in the genome stabilization procedure leads to phenotypic variability and can generate additional diversity after the initial hybridization process. Moreover, several stabilized hybrids showed phenotypes that are interesting for industrial applications.